1992
DOI: 10.1063/1.106477
|View full text |Cite
|
Sign up to set email alerts
|

Molecular layer etching of GaAs

Abstract: Layer-by-layer controlled molecular layer self-limiting etching at one molecular layer of GaAs was successfully achieved for the first time by alternatively feeding an etchant of Cl and applying a low energy Ar ion beam to the GaAs substrate. The etching rate saturates exactly at one molecular layer per cycle and is independent of etchant feeding rate and the energetic ion beam flux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(34 citation statements)
references
References 7 publications
0
34
0
Order By: Relevance
“…Steps 2 and 4 are purge steps. Since then, a large set of publications has appeared in scientific literature and the method has come to be known by a variety of other names, namely digital etching, 21 layer-by-layer etching, 22 molecular-layer etching, 23 plasma atomic layer etching (PALE), 24 etc. Yet, the original name of "atomic layer etching" coined in the first patent has remained most popular.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
“…Steps 2 and 4 are purge steps. Since then, a large set of publications has appeared in scientific literature and the method has come to be known by a variety of other names, namely digital etching, 21 layer-by-layer etching, 22 molecular-layer etching, 23 plasma atomic layer etching (PALE), 24 etc. Yet, the original name of "atomic layer etching" coined in the first patent has remained most popular.…”
Section: The Early Days Of Atomic Layer Etchingmentioning
confidence: 99%
“…61,62 They published subsequently additional work using Ar ion bombardment, 63 or photon irradiation of a chlorine-coated GaAs surface. 44,64 Aoyagi et al 65 studied GaAs ALE using alternating Cl 2 exposure and synchronized low energy Ar + bombardment by applying a low bias voltage in an electron cyclotron resonance (ECR) plasma system. The ECR Ar discharge was continuously maintained, and Cl 2 was admitted for times up to 40 s to achieve adsorption of Cl atoms at the GaAs surface.…”
Section: Atomic Layer Etching Of Various Materials -A Brief Surveymentioning
confidence: 99%
“…Park et al 3 have reported a similar mechanism for atomic z E-mail: satyarth.suri@intel.com layer removal of Si using a combination of Cl 2 adsorption and Ne neutral beam. Such atomic layer etching processes have also been reported for GaAs 5 and Ge. 7 It is important to note here that exposure with energetic radicals or use of energetic ions may result in damage or modification of the next layer of atoms, thereby eliminating one of the potential benefits (damage-free processing) of ALEt.…”
Section: What Is Atomic Layer Etching?mentioning
confidence: 97%
“…The idealized sequence described in Figure 1a-1d enables formation of an anisotropic atomic layer removal of material. Several reports are present in the literature [2][3][4][5][6][7][8] where variations of the idealized flow have been successfully demonstrated. A requirement for this flow, and hence somewhat of a limitation, is that the modified surface layer released during the process in Figure 1c should be a stable volatile by-product so that it can be efficiently pumped out of the process chamber.…”
Section: What Is Atomic Layer Etching?mentioning
confidence: 99%
See 1 more Smart Citation